2011
DOI: 10.1111/j.1439-0434.2011.01787.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Changes in Downy Mildew‐infected Sunflower Triggered by Resistance Inducers

Abstract: In the present study, the mechanism of resistance to Plasmopara halstedii, the downy mildew pathogen of sunflower, triggered by three resistance-inducing chemicals, benzo (1,2,3) thiadiazole-7-carbothioic acid S-methyl ester (BTH), DL-b-amino butyric acid (BABA) and 2,6-dichloroisonicotinic acid (INA), was investigated in susceptible, completely resistant and partially resistant sunflower genotypes. By applying P. halstediispecific primers, no detectable pathogen marker transcript accumulation was found in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
(62 reference statements)
1
8
0
Order By: Relevance
“…BTH has been shown to activate resistance in many crops against a broad spectrum of diseases such as powdery mildew in barley and wheat [11], pea rust [4] and Sclerotinia diseases in melon [5] and soybean [8]. Similar activity was found to occur in sunflower against downy mildew [3,14,24] and rust disease [20].…”
Section: Introductionmentioning
confidence: 99%
“…BTH has been shown to activate resistance in many crops against a broad spectrum of diseases such as powdery mildew in barley and wheat [11], pea rust [4] and Sclerotinia diseases in melon [5] and soybean [8]. Similar activity was found to occur in sunflower against downy mildew [3,14,24] and rust disease [20].…”
Section: Introductionmentioning
confidence: 99%
“…These results are in accordance with our previous analysis on the comportment of FU in the growth chamber (SAKR, 2011a;SAKR et al, 2011). Thus our observation suggests that in inbred line FU, the development of the pathogen was slowed, and may be due to resistance mechanisms expressed by accumulation of QTL in sunflower cultivars or presence of resistance-inducing chemicals which improve resistance in sunflower genotypes to downy mildew and increase enzyme activities (KÖRÖSI et al, 2011). Differences in aggressiveness of P. halstedii isolates are indicated when isolates vary in the degree of damage that they can cause in sunflower plants (SAKR, 2011a, b andc, 2012;SAKR et al, 2011).…”
Section: Discussionmentioning
confidence: 77%
“…In Hungary, investigations have been made on the expression of genes allegedly associated with resistance response by measuring the accumulation of the transcripts of glutathion-S-transferase (GST), defensin (PDF), and catalase (CAT) following treatments with benzothiadiazole (BTH), dichloroisonicotinic acid (INA), or beta-aminobutyric acid (BABA) and/or P. halstedii inoculation. Preliminary results revealed significant increases in the activity of these genes in the susceptible but not in the resistant sunflowers, whereas the results with the partially resistant (HLI-type) sunflower were contradictory (Körösi and Virányi 2008). Apart from the plant activators, mentioned above, Nandeeshkumar et al (2008a) reported about an enhanced and early activation of defence-related responses to downy mildew in a susceptible sunflower cultivar treated with chitosan.…”
Section: Induced Resistancementioning
confidence: 92%